2022
DOI: 10.1590/2317-1782/20212020326
|View full text |Cite
|
Sign up to set email alerts
|

Adesão ao uso do Sistema de Microfone Remoto em estudantes com deficiência auditiva usuários de dispositivos auditivos

Abstract: RESUMO Objetivo Identificar relações entre a utilização sistemática do Microfone Remoto (MR) em sala de aula de estudantes com deficiência auditiva e características das escolas e dos professores. Método Foram analisados 120 sujeitos, entre cinco e 17 anos, com deficiência auditiva que foram adaptados MR em um Serviço de Saúde credenciada pelo Sistema Único de Saúde (SUS). Também foram sujeitos, professores de usuários de MR. Realizou-se uma análise de prontuários e no momento que os sujeitos compareceram pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Implementation of an RMS can sometimes result in dramatic changes in behavior, participation and academic learning that are readily identifiable. However, sometimes the effects of an RMS can be subtler, for example, faster response times to questions posed by the classroom teacher, less fatigue at the end of the day or a greater willingness to participate in discussions [122][123][124][125][126]. A listening checklist can focus the respondent's attention on aspects of listening and learning that they had not considered previously.…”
Section: Evaluating Benefits Of Access Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation of an RMS can sometimes result in dramatic changes in behavior, participation and academic learning that are readily identifiable. However, sometimes the effects of an RMS can be subtler, for example, faster response times to questions posed by the classroom teacher, less fatigue at the end of the day or a greater willingness to participate in discussions [122][123][124][125][126]. A listening checklist can focus the respondent's attention on aspects of listening and learning that they had not considered previously.…”
Section: Evaluating Benefits Of Access Technologiesmentioning
confidence: 99%
“…Unwillingness to access and use technology by deaf students of all ages has been reported often, even when students articulate its usefulness [117,[124][125][126]. Compliance with using RMS at school has been reported to be higher in elementary grades than in high school, due largely to social factors and the desire not to look different from peers [124][125][126]. Esturaro et al [125] found that in their sample of 120 students with RMS, only slightly more than half (54%) were using it.…”
Section: Willingness and Ability To Use Technologymentioning
confidence: 99%
See 1 more Smart Citation